A Systematic Literature Review on Business Intelligence from A Decision-Making Perspective - Jhonatan GALLARDO-ALCANTARA; Gerson NAPA-FUENTES; Javier GAMBOA-CRUZADO; Edward RUBIO-LUNA VICTORIA; Alberto ALVA-ARÉVALO; Caleb RÍOS-VARGAS; Mauro CRUZADO-VIERA (Communications of International Proceedings, 2021)
Nowadays, it can be stated that business intelligence (BI) has become one of the trends that companies are adopting to make optimal decisions. Very few companies choose to implement BI because they usually have no knowledge to get started in that area. In such context, this study was conducted to provide necessary information to know the different elements that must be taken into account when implementing BI in any organization. This study is based on the methodology known as systematic literature review, that is, reviews of different articles related to a research topic, in particular scientific papers. In addition, different exclusion and quality criteria were established with the aim of obtaining information from different sources of papers that provided as much useful information as possible for the development of this manuscript. The results obtained in this study were compared with similar studies to corroborate and improve our research, thereby providing more useful results that can serve as a basis for future studies.
Keywords: Business Intelligence; Decision-Making; Systematic Literature Review; Information; Data.